Morphophysiological impacts on Luffa cylindrica (L.) M. Roem. as affected by Paclobutrazol and CO 2 -enriched atmosphere - Dutra, Quezia Pains (2024)
Morphophysiological impacts on Luffa cylindrica (L.) M. Roem. as affected by Paclobutrazol and CO 2 -enriched atmosphere. Advisor: Wagner Campos Otoni. Co-Advisor: Tatiane Dulcineia Silva. The plant life cycle involves various strategies to resume growth and development by sensing internal and environmental cues. The environment significantly influences plant metabolism, affecting the production of primary and secondary metabolites. High concentrations of atmospheric CO 2 , among other factors, such as compounds called stress relievers, can trigger the production of specific compounds, influencing functional structures such as vascular tissues. The xylem tracheary elements (TEs) undergo a highly regulated differentiation process involving dedifferentiation, redifferentiation, and programmed cell death, resulting in lignified secondary walls. Luffa cylindrica, a Cucurbitaceae, shows elevated investment in growth and vascular differentiation to sustain the high ovary development rates that culminate in large fruits with typical richness in lignocellulosic fibers. We aimed to investigate the morphophysiological, biochemical, and molecular impacts in plants of the target species exposed in vitro to Paclobutrazol (PBZ) concentrations (0 – control; 0.21; 0.42; 0.85; 1.7; and 3.4 µM); and to CO 2 -enriched atmospheres in open-top chambers {ambient - a[CO 2 ] (± 400 µM mol -1 ) and enriched - e[CO 2 ] (± 800 µM mol -1 ). Regarding PBZ, as expected, this growth regulator promoted alteration in plant growth, reducing stem and root size. Likewise, the leaves were smaller, more pigmented, and thicker. As a result, the photosynthetic rate decreased at dosages of 1.7 and 3.4 µM of PBZ. In addition, changes in morphology were observed, such as an increase in the area of the vessels of the metaxylem and mesophyll at higher concentrations and the vascular bundle area. PBZ at concentrations of 0.85, 1.7, and 3.4 µM also increased the activity of the antioxidative enzymes, namely Catalase and Peroxidase, as well as lipid peroxidation (as indicated by MDA). There was also an increase in the expression of genes involved in the biosynthesis of polyamines, Thermospermine synthase (LcACL5), Polyamine oxidase (LcPAO), Spermidine synthase (LcSPDE) at the higher concentrations, as well as an increase in Cinnamyl alcohol dehydrogenase (CAD), involved in the lignin biosynthesis pathway. Regarding CO 2 enrichment, e[CO 2 ] significantly increased plant height and root length. Over time, there was also an increase in dry and fresh mass, biomass, and specific leafarea. The analyzed enzymes CAT, SOD, POD, and APX did not change. Concerning sugar content, an increase was observed after 25 days of experimentation with high CO 2 . The availability of CO 2 promoted an increase in carbohydrates, which are mobilized for the biosynthesis of essential compounds for plant growth and development. The genes' expression in the lignin (Cafeato o-methyltransferase - COMT) and polyamine biosynthesis (ACL-5) pathways were positively regulated. These changes in growth and biochemistry allow us to understand that, at high CO 2 concentrations, there is a photosynthetic efficiency that favors the growth and development of this species. The high adaptive efficiency and the reorganization of its metabolism allow this species to survive the future scenario of an environment with high CO 2 concentrations. This study plays an exploratory role in understanding the effects of climate change and its wide-range implications in various areas, such as agricultural adaptations, biodiversity conservation, and human health.